A Simulation of Hydrogen Adsorption/Desorption in Metal-Functionalized BN Nanotube - Mananghaya, Michael Rivera (Archīum Ateneo, 2019)
Ti-decorated (10,0) single-walled BN nanotubes (BNNTs) with B–N defects was fully examined by density functional theory (DFT) and molecular dynamics (MD) simulation. According to DFT formalisms, the Ti atom does not form any clusters and protrudes to the external surface of the BNNT. The calculations suggest that the Ti-BNNT assembly can attract up to seven H2 per Ti. The unaltered H–H bond distance along with a poor molecular orbital (HOMO and LUMO) overlap with the Titanium-BN nanotube for succeeding hydrogen adsorption (>7H2 per Ti) precludes that the system is saturated. The MD simulations revealed that the adsorption of H2 can take place on the surface and interstitial sites of the Ti/BNNT with a corresponding gravimetric hydrogen uptake of >7.0 wt%. Further, the resulting pressure of the system is significantly reduced with high H2 uptake. The simulation also suggests that with proper temperature control, the charging and releasing of H2 can be well regulated. Finally, the structure is barely perturbed upon adsorption/desorption and the hydrogen storage capacity is in compliance with the Department of Energy specifications.